Non-indigenous species in Portuguese coastal areas, coastal lagoons, estuaries and islands. (20th December 2015) - Chainho, Paula; Fernandes, António; Amorim, Ana; Ávila, Sérgio P.; Canning-Clode, João; Castro, João J.; Costa, Ana C.; Costa, José L.; Cruz, Teresa; Gollasch, Stephan; Grazziotin-Soares, Clarissa; Melo, Ricardo; et al.
Abstract: Trends in abundance, temporal occurrence and spatial distribution of marine and brackish non-indigenous species (NIS) are part of the indicators to assess the compliance of Good Environmental Status in the European Marine Strategy Framework Directive (EU-MSFD). European-wide regional and national databases for NIS will be useful for the implementation of the EU-MSFD but there are still spatial gaps for some regions and taxonomic groups. In 2009, Portugal was among the countries with the lowest reported numbers of NIS in Europe and a national online database on NIS was not available. This study provides an updated list of NIS registered in Portuguese coastal and estuarine waters, including mainland Portugal and the Azores and Madeira archipelagos. A list of 133 NIS was cataloged, most of which recorded in the last three decades, showing that this area of the North Atlantic is no less prone to introductions than neighboring areas. Most NIS reported in the current inventory are native in the Indo-Pacific region. Fouling and ballast water are the most likely introduction vectors of NIS in the studied area but shipping routes connecting to the NIS native regions are rare, indicating that most species are secondary introductions. The high number of NIS in the Azores and Madeira islands indicates that this ecosystem type seems to be more susceptible to invasions but these preliminary results might be biased by a higher number of studies and knowledge on the NIS occurrence on the islands. Highlights: A checklist of the non-indigenous species occurring in Portugal was provided. Population status, native distribution and introduction vectors were indicated. Invasion patterns of islands, estuaries, coastal areas and lagoons were examined. Temporal trends of introductions were analysed.